Evaluating rates of reporting symptoms of Parkinson's disease psychosis: provider versus targeted questionnaire. (4th May 2022) - Greger, Jessica; Aladeen, Traci; Rainka, Michelle; Kale, Anupama; Capote, Horacio
Abstract: Purpose/aim: A targeted questionnaire may help increase rates of reporting Parkinson's disease psychosis (PDP) symptoms. Despite the need for a rapid patient- and/or caregiver-administered screening tool for PDP symptoms, an appropriate tool is not yet available. This study developed a targeted PDP questionnaire and examined rates of reporting psychosis symptoms in response to the questionnaire compared to rates of reporting symptoms to healthcare providers during a routine visit. Materials and methods: This was a single-center, cross-sectional observational study of patients at an outpatient neurology practice. Medical charts were screened for eligibility, and patients were contacted by telephone for informed consent. Results: A total of 25 patients (24%, N  = 104) newly reported PDP symptoms in response to the targeted questionnaire. The frequency of reporting new symptoms in response to the questionnaire was statistically significantly greater compared to frequency of reporting symptoms without use of a targeted questionnaire ( p  < 0.0001). Conclusions: A targeted questionnaire increases rates of reporting PDP symptoms, and based on frequency, severity, and distress ratings, may allow for capture of PDP symptoms earlier in the course of the disease. By using a questionnaire, patients reported symptom onset an average of 1.4 years earlier than patients who reported symptoms to their providers according to patient medical records.